The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ccd.29639
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication of right ventricular dysfunction and tricuspid regurgitation following transcatheter aortic valve replacement

Abstract: Objectives Right ventricular (RV) dysfunction and tricuspid regurgitation (TR) are associated with adverse outcomes in severe aortic stenosis (AS) patients. Our aim was to evaluate the association between ≥moderate TR and RV dysfunction on long‐term mortality following transcatheter aortic valve replacement (TAVR). Methods A retrospective analysis of the Israeli multicenter TAVR registry among 4,344 consecutive patients, with all‐cause mortality as the main outcome measure. Results Echocardiographic assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Moreover, the degree of TR could significantly change after TAVI due to improvement of the hemodynamics at the left sided heart. As such there are still conflicting data on the prognostic value of baseline TR in patients undergoing TAVI [3,12,15]. However, we found that persistence of more than mild TR after TAVI to be predictive of worse long-term outcomes, which strengthens previous study results [3,15].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, the degree of TR could significantly change after TAVI due to improvement of the hemodynamics at the left sided heart. As such there are still conflicting data on the prognostic value of baseline TR in patients undergoing TAVI [3,12,15]. However, we found that persistence of more than mild TR after TAVI to be predictive of worse long-term outcomes, which strengthens previous study results [3,15].…”
Section: Discussionsupporting
confidence: 82%
“…There is a growing body of evidence about the impact of RV dysfunction on mortality after TAVI [3,8,9]. However, conventional echocardiographic parameters for assessment of RV function have demonstrated conflicting results with respect to their association with mortality after TAVI [10][11][12]. The advantage of RV free-wall LS assessed by STE over conventional echocardiographic parameters has been demonstrated by Scheuler et al [13] and by Medvedovsky et al [14] reporting a significant association with mortality after TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, clinically relevant TR has been shown to improve in 15% to 60% of patients undergoing TAVR (4,5,9,10,22). In contrast, owing to the dynamic and load dependent nature of TR, progression of TR after TAVR has been reported in 4%-11% of patients with nonsignificant TR at baseline (4,5,23). Previous studies suggested that persistent or worsening of moderate or greater TR was associated with an increased risk of mortality (6,9,10,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, owing to the dynamic and load dependent nature of TR, progression of TR after TAVR has been reported in 4%-11% of patients with nonsignificant TR at baseline (4,5,23). Previous studies suggested that persistent or worsening of moderate or greater TR was associated with an increased risk of mortality (6,9,10,22,23). Consistent with these studies, more than half of patients with significant baseline TR had an improvement of at least one grade after TAVR, while a small proportion of patients (5% to 7%) with baseline <massive TR had a progression in the TR severity after TAVR in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…39 Right ventricular dysfunction recovery has been reported in 50-59% of patients following TAVR and has been associated with significantly lower rates of all-cause and cardiovascular death compared with patients with ongoing RVD post-procedure. [36][37][38]40 In the Israeli multicentre TAVR registry, the absence of RVD recovery post-TAVR posed the greatest long-term mortality risk (HR 3.33, 95% CI 1.95-5.7). 40…”
Section: Transcatheter Aortic Valve Replacement In Patients With Righ...mentioning
confidence: 99%